Association of Cataract Surgery in Diabetic Patients with the Progression of Diabetic Retinopathy: A Systematic Review of Randomized Controlled Trials and Primary Studies - Sri Adinda Ayu; Gunawan (The Indonesian Journal of General Medicine, 2026)
Introduction: Cataract surgery is one of the most frequently performed ophthalmic procedures worldwide, and diabetes mellitus (DM) is a major risk factor for cataract development. Diabetic retinopathy (DR), a leading cause of preventable blindness, may be adversely affected by cataract surgery through inflammatory cascade activation and disruption of the blood-retinal barrier. However, the magnitude and clinical significance of this risk remain subjects of ongoing debate. This systematic review aims to synthesize evidence from randomized controlled trials (RCTs) and primary studies examining the association between cataract surgery and DR progression in diabetic patients. Methods: A systematic review adhered to the Preferred Reporting Items for Systematic Review and  (PRISMA) 2020 guidelines. Studies including adult diabetic patients undergoing cataract surgery with outcomes related to DR progression, diabetic macular edema (DME), best-corrected visual acuity (BCVA), and central macular thickness (CMT) were included. Quality assessment used the Cochrane Risk of Bias tool (RoB 2) for RCTs and the Newcastle-Ottawa Scale (NOS) for observational studies. A total of 17 studies (7 RCTs and 10 primary/observational studies) comprising 25,634 eyes were included. Results: DR progression was significantly higher after cataract surgery compared to non-operated fellow eyes or control cohorts (Risk Ratio [RR] 1.46; 95% CI: 1.28–1.66; P < 0.001). Anti-VEGF prophylaxis at the time of cataract surgery significantly reduced DR progression (RR 0.37; 95% CI: 0.19–0.70; P = 0.002) and improved BCVA. Intravitreal dexamethasone implants reduced CMT and decreased the need for rescue interventions. Risk factors associated with postoperative DR progression included elevated HbA1c, duration of DM, and severity of preoperative DR. The incidence of postoperative DME ranged from 6.06% to 46.2% depending on baseline DR severity. Discussion: Surgery-induced inflammation, VEGF upregulation, and breakdown of the blood-ocular barrier are the primary mechanisms underlying DR progression post-cataract surgery. Modern phacoemulsification carries a lower risk compared to earlier techniques; however, the risk remains clinically significant in patients with more advanced baseline DR. Prophylactic anti-VEGF or corticosteroid intravitreal injections at the time of surgery offer meaningful protection against DR worsening and postoperative DME. HbA1c optimization and preoperative DR control are critical to mitigating surgical risk. Conclusion: Cataract surgery in diabetic patients is associated with a statistically significant increased risk of DR progression, particularly in those with moderate-to-severe NPDR or poorly controlled glycemia. Prophylactic intravitreal anti-VEGF or corticosteroid therapy at the time of surgery is effective in reducing postoperative DR progression and DME. Preoperative optimization of systemic control and early postoperative monitoring are strongly recommended.